Can we apply the results of the Steroid Corneal Ulcer Trial to Nocardia infections of the cornea?. (February 2013) - Garg, Prashant; Vazirani, Jayesh
Evaluation of: Lalitha P, Srinivasan M, Rajaraman R et al . Nocardia keratitis: clinical course and effect of corticosteroids. Am. J. Ophthalmol. 154(6), 934.e1–939.e1 (2012). The authors compared the clinical course of Nocardia species keratitis with keratitis resulting from other bacterial organisms and also the effect of corticosteroids as adjunctive therapy. This was a subgroup analysis using data collected from the Steroid Corneal Ulcer Trial wherein 500 patients with culture‑proven bacterial keratitis were randomized 1:1 to topical corticosteroid therapy or placebo after receiving topical moxifloxacin therapy for at least 48 h. Fifty five patients presented with Nocardia keratitis and the data from these patients were used for the subgroup analysis. The authors analyzed various aspects of Nocardia keratitis and compared several features with non- Nocardia keratitis cases. Since 31 subjects of the subgroup were randomized to corticosteroid therapy and 23 to the placebo group, the data could be used to study the effect of corticosteroids for Nocardia keratitis. The key findings of this study were as follows: trauma was the most common predisposing factor for this infection, and nearly half of the enrolled subjects were agricultural workers; the patients with Nocardia ulcers had longer duration of symptoms (median duration of 10 vs 4 days for non- Nocardia cases); despite longer duration of symptoms, the patients had better presenting visual acuity (median Snellen visual acuity 20 out of 45 compared with 20 out of 145 for non- Nocardia cases) while the infiltrate size remained the same (median infiltrate size: 2.7 mm); the most common species were Nocardia cyriacigeorgica (35%), Nocardia pneumoniae (21%) and Nocardia asteroides (19%); 98% of the Nocardia species were susceptible to amikacin while fluoroquinolones showed variable activity; median best spectacle corrected visual acuity and infiltrate or scar size at 3 months were comparable with non- Nocardia keratitis cases; on average, the use of corticosteroids was associated with a 0.40-mm larger infiltrate or scar size at 3 months in Nocardia keratitis cases, however, there was no difference in the time to re‑epithelialisztion and rate of corneal perforation. The authors concluded that Nocardia keratitis generally responds well to antibiotic therapy, but the adjunctive use of corticosteroids results in larger infiltrate or scar sizes, suggesting that this therapy may not be appropriate for treating this disease.